Policy making and implementation : studies from Papua New Guinea - May, R. J. (Ronald James), 1939- (Studies in state and society in the Pacific, 2009)
"This volume, which brings together a number of Papua New Guinean and Australian-based scholars and practitioners with deep familiarity of policy making in Papua New Guinea, examines the record of policy making and implementation in Papua New Guinea since independence. It reviews the history of public sector reform in Papua New Guinea, and provides case studies of policy making and implementation in a number of areas, including the economy, agriculture, mineral development, health, education, lands, environment, forestry, decentralization, law and order, defence, women and foreign affairs, privatization, and AIDS."--Publisher's description